TAUHID DAN ISLAM: Implementasi Pendidikan Tauhid di Sekolah - Anwar, Lucy; Sadari, Sadari; Khotimah, Husnul (Moderation | Journal of Islamic Studies Review, 2025)
This article discusses the importance of monotheism (tauhid) in the diversity of humanity and its role in social systems and worship. The research objective is to understand tauhid education as an integral part of Islamic education leading to the recognition of God. The method used is qualitative descriptive with a literature study approach, collecting data from books, the Qur'an, and related literature. The findings indicate that tauhid education is essential in shaping individuals who recognize the oneness of God and avoid polytheism, contributing to the unity of humanity. In conclusion, tauhid is the foundation of Islamic civilization that teaches that only Allah is worthy of worship, and tauhid education in schools is expected to strengthen students' beliefs and prevent misunderstandings.